2020
DOI: 10.3390/rs12244012
|View full text |Cite
|
Sign up to set email alerts
|

Lookup Table Approach for Radiometric Calibration of Miniaturized Multispectral Camera Mounted on an Unmanned Aerial Vehicle

Abstract: Over recent years, miniaturized multispectral cameras mounted on an unmanned aerial vehicle (UAV) have been widely used in remote sensing. Most of these cameras are integrated with low-cost, image-frame complementary metal-oxide semiconductor (CMOS) sensors. Compared to the typical charged coupled device (CCD) sensors or linear array sensors, consumer-grade CMOS sensors have the disadvantages of low responsivity, higher noise, and non-uniformity of pixels, which make it difficult to accurately detect optical r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
(56 reference statements)
0
13
0
Order By: Relevance
“…Due to sensor degradation, these values are likely to gradually decline over time, lessening the accuracy of the radiometric calibration processing (Mamaghani and Savaggio, 2019). Studies have improved sensor performance by performing vicarious radiometric calibration using ground targets and panels with known radiometric accuracy, calibrating sensors using National Institute of Standards (NIST)-traceable equipment in a laboratory, and developing look-up tables for correction factors to update calibration parameters (Del Pozo et al, 2014;Mamaghani and Salvaggio, 2019;Cao et al, 2020). Baek et al (2020) conducted an assessment on radiometric accuracy for the MicaSense RedEdge-MX sensor by comparing data to hyperspectral sensors with NIST-traceable calibration (TriOS RAMSES) and showed that MicaSense RedEdge-MX radiance is approximately 5-16% lower, and irradiance is approximately 1-20% lower, depending on wavelength (Baek et al, 2020).…”
Section: Uas Sensor Considerationsmentioning
confidence: 99%
“…Due to sensor degradation, these values are likely to gradually decline over time, lessening the accuracy of the radiometric calibration processing (Mamaghani and Savaggio, 2019). Studies have improved sensor performance by performing vicarious radiometric calibration using ground targets and panels with known radiometric accuracy, calibrating sensors using National Institute of Standards (NIST)-traceable equipment in a laboratory, and developing look-up tables for correction factors to update calibration parameters (Del Pozo et al, 2014;Mamaghani and Salvaggio, 2019;Cao et al, 2020). Baek et al (2020) conducted an assessment on radiometric accuracy for the MicaSense RedEdge-MX sensor by comparing data to hyperspectral sensors with NIST-traceable calibration (TriOS RAMSES) and showed that MicaSense RedEdge-MX radiance is approximately 5-16% lower, and irradiance is approximately 1-20% lower, depending on wavelength (Baek et al, 2020).…”
Section: Uas Sensor Considerationsmentioning
confidence: 99%
“…However, the spectrometer's accuracy will be affected by a variety of error sources. The main error sources are the stray light error [19][20][21] and the detector non-uniformity error [22][23][24]. These errors make the equation AX = B unsuitable and add difficulty obtaining a solution for the equation.…”
Section: ( ) ( )mentioning
confidence: 99%
“…The LUT method provides a correction factor for each pixel and has the highest accuracy for vignetting correction. It is a common method to generate the LUT for vignetting correction, where reference images obtained under uniform illumination are used to extract the vignetting background [7,16]. Subsequently, the vignetting background is used to generate the LUT, which is typically the ratio of the maximum value of the reference image to the value of each pixel, given the impact of image noise.…”
Section: Introductionmentioning
confidence: 99%